Alpha‐synuclein transfers from neurons to oligodendrocytes. Issue 3 (31st December 2013) - Reyes, Juan F.; Rey, Nolwen L.; Bousset, Luc; Melki, Ronald; Brundin, Patrik; Angot, Elodie
<x xml:space="preserve">Abstract</x> The origin of α‐synuclein (α‐syn)‐positive glial cytoplasmic inclusions found in oligodendrocytes in multiple system atrophy (MSA) is enigmatic, given the fact that oligodendrocytes do not express α‐syn mRNA. Recently, neuron‐to‐neuron transfer of α‐syn was suggested to contribute to the pathogenesis of Parkinson's disease. In this study, we explored whether a similar transfer of α‐syn might occur from neurons to oligodendrocytes, which conceivably could explain how glial cytoplasmic inclusions are formed. We studied oligodendrocytes in vitro and in vivo and examined their ability to take up different α‐syn assemblies. First, we treated oligodendrocytes with monomeric, oligomeric, and fibrillar forms of α‐syn proteins and investigated whether α‐syn uptake is dynamin‐dependent. Second, we injected the same α‐syn species into the mouse cortex to assess their uptake in vivo. Finally, we monitored the presence of human α‐syn within rat oligodendroglial cells grafted in the striatum of hosts displaying Adeno‐Associated Virus‐mediated overexpression of human α‐syn in the nigro‐striatal pathway. Here, we show that oligodendrocytes take up recombinant α‐syn monomers, oligomers and, to a lesser extent, fibrils in vitro in a concentration and time‐dependent manner, and that this process is inhibited by dynasore. Further, we demonstrate in our injection model that oligodendrocytes also internalize α‐syn in vivo. Finally, we provide the first direct evidence that α‐syn can transfer to grafted oligodendroglial cells from host rat brain neurons overexpressing human α‐syn. Our findings support the hypothesis of a neuron‐to‐oligodendrocyte transfer of α‐syn, a mechanism that may play a crucial role in the progression and pathogenesis of MSA. GLIA 2014;62:387–398